PC hardware in a nutshell - Thompson, Robert Bruce (O'Reilly, 2002)
Carefully researched and written, PC Hardware in a Nutshell, 2nd Edition is packed with useful and unbiased information, including how-to advice for specific components, ample reference material, and a comprehensive case study on building a PC. To the point yet complete, this book provides an enormous amount of timeless information intended for anyone who buys, builds, upgrades, or repairs PCs in a corporate, small business, or home setting. In addition to coverage of the fundamentals and general tips about working on PCs, this book includes chapters focusing on motherboards, processors, memory, floppies, hard drives, optical drives, tape devices, video devices, input devices, audio components, communications, power supplies, and maintenance. Special emphasis is given to upgrading and troubleshooting existing equipment so you can get the most from your existing investments. This new edition is expanded to include: Detailed information about the latest motherboards and chipsets from AMD, Intel, SiS, and VIA Extensive coverage of the Pentium 4 and the latest AMD processors, including the Athlon XP/MP Full details about new hard drive standards, including the latest SCSI standards, ATA/133, Serial ATA, and the new 48-bit "Big Drive" ATA interface Extended coverage of DVD drives, including DVD-RAM, DVD-R/RW, and DVD+R/RW Details about Flat Panel Displays, including how to choose one (and why you might not want to) New chapters on serial communications, parallel communications, and USB communications (including USB 2.0) Enhanced troubleshooting coverage PC Hardware in a Nutshell, 2nd Edition provides independent, useful and practical information in a no-nonsense manner with specific recommendations on components. Based on real-world testing over time, it will help you make intelligent, informed decisions about buying, building, upgrading, and repairing PCs in a cost effective manner that will help you maximize new or existing computer hardware systems
Print version record
Keywords: Microcomputers -- Equipment and supplies; Microcomputers -- Upgrading; Microcomputers -- Maintenance and repair; Microcomputers -- Purchasing; Micro-ordinateurs; Appareils et matériel; Micro-ordinateurs; Mise à niveau; Micro-ordinateurs; Entretien et réparations; Micro-ordinateurs; Achat; Microcomputers; Equipment and supplies; Microcomputers; Maintenance and repair; Microcomputers; Purchasing; Microcomputers; Upgrading